2020
DOI: 10.21203/rs.3.rs-89832/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face mask use among pedestrians during the COVID-19 pandemic in southwest Iran: An observational study on 10440 people

Abstract: Background: Many countries have recommended the use of face masks for general population in public places to reduce the risk of COVID-19 transmission. This study aims to estimate the prevalence of face mask usage and investigate about different types of face mask and their distribution among pedestrians in southwest Iran during the Covid-19 pandemic.Methods: This cross-sectional study was conducted in August 2020 in Ahvaz, southwest Iran. Using a multistage sampling method, a total of 10440 pedestrians selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
3
2
Order By: Relevance
“…In our study, surgical masks were used more than other types (70.7%). This result is similar to previous studies results [4][5][6]. Although ltered masks and N95 have a greater protective effect than surgical masks, according to the World Health Organization, surgical masks are more suitable for general use [3].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, surgical masks were used more than other types (70.7%). This result is similar to previous studies results [4][5][6]. Although ltered masks and N95 have a greater protective effect than surgical masks, according to the World Health Organization, surgical masks are more suitable for general use [3].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, women used masks more than men (67.5% vs. 46.7%, p < 0.001). In the same study conducted in Ahvaz, this rate in females was higher than males (60.2% vs. 38.7%, p < 0.001) [4]. This may indicate that the woman is paying more attention to her health and following her health instructions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Facemask usagewas signi cantly higher in males than in females in this study. This is in contrastwith a study in Saudi Arabia and in south Asian countries where there was higher usage amongst females than males [21,23]. This contrast may be as a result of difference in cultural orientation particularly among femalesin the respective parts of the world.…”
Section: Discussioncontrasting
confidence: 86%
“…The highest rate of facemasks usage/adherence was observed amongst the adolescentsthan people in other age categories. This is in contrast with previous studies which found adults to use facemasks more than adolescents [9,23]. Access to COVID-19 information especially through the internet is more common among the adolescents; this may have played an important role in in uencing the facemasks usage among them [9].…”
Section: Discussioncontrasting
confidence: 80%